Gambaran Tingkat Kepuasan Pasien terhadap Pelayanan Informasi Obat di Apotek Wilayah Lombok Timur - Hartono, M. Herry; Oktresia, Erma Ewisa; Sovia, Fitriwati (Sinteza, 2023)
Pharmaceutical services are a direct and responsible service to patients. One of the pharmaceutical service activities that align with the concept of pharmaceutical care is found in the quality of Drug Information Services (PIO) in pharmacies. The aim of this research is to determine the implementation of DIS based on the Indonesian Minister of Health Regulation No.73 of 2016 in pharmacies in the East Lombok region. This study is observational descriptive using quantitative analysis in the form of calculating the percentage of Respondent Achievement Level (TCR). Data was collected using a questionnaire covering eight activities that pharmacists should undertake when providing drug information, which were subsequently used as indicators. Sample selection was done through purposive sampling with a minimum of 96 samples. Based on the research results, the TCR percentage values for the indicators were as follows: information on drug efficacy at 78% with a good category; dosage form at 78% with a good category; usage instructions at 75% with a good category; drug dosage at 74% with a good category; side effects at 74% with a good category; drug storage at 74% with a good category; safety for pregnant and nursing mothers at 46% with a fair category; information on drug prices obtained a score of 90% with a very good category. The average TCR score for the 8 indicators was 73.3% with a good category in providing drug information services in accordance with the Indonesian Minister of Health Regulation No.73 of 2016 in pharmacies in the East Lombok region.